2015
DOI: 10.1155/2015/294523
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model of Kaplan Turbine Regulating System Suitable for Power System Analysis

Abstract: Accurate modeling of Kaplan turbine regulating system is of great significance for grid security and stability analysis. In this paper, Kaplan turbine regulating system model is divided into the governor system model, the blade control system model, and the turbine and water diversion system model. The Kaplan turbine has its particularity, and the on-cam relationship between the wicket gate opening and the runner blade angle under a certain water head on the whole range was obtained by high-order curve fitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Several methods are typically used to reflect the key parameters at each moment in the flow field in the flow channel. One is to use the one-dimensional method of characteristics (1D-MOC) [1,5] and transfer function method (TFM) [6] et al to establish a numerical model of the entire flow channel of the turbine. The 1D transient process analysis simplifies the complicated water diversion system and equipment into simple pipelines and simplified models.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are typically used to reflect the key parameters at each moment in the flow field in the flow channel. One is to use the one-dimensional method of characteristics (1D-MOC) [1,5] and transfer function method (TFM) [6] et al to establish a numerical model of the entire flow channel of the turbine. The 1D transient process analysis simplifies the complicated water diversion system and equipment into simple pipelines and simplified models.…”
Section: Introductionmentioning
confidence: 99%
“…Energies 2021, 14, 2604 2 of 15 Results from Zhao et al [7] have shown that small turbines present lots of potential for generating high-efficiency hydropower, whilst also showing increased flexibility over larger turbines during times of lower power demand.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, the measured data composed of different heads and loads under various working conditions can be combined with appropriate algorithms to construct more accurate nonlinear hydraulic turbine models. These models have been extended to the single-regulation nonlinear model proposed by IEEE in 1992 [15], which means that the blade adjustment part can be added without modifying the basic model equations, and it has higher flexibility [16]- [18]. Although these studies have improved the Kaplan turbine model accuracy, the single-regulated control method with a combined relationship curve is still employed in practical application, and the transient process's adjustment problem still exists.…”
Section: Introductionmentioning
confidence: 99%